PENGARUH PERCEIVED BRAND INFORMATION QUALITY TERHADAP UNVERIFIED INFORMATION SHARING BEHAVIOR MELALUI ATTITUDE TOWARDS VERIFYING INFORMATION DI MEDIA SOSIAL TWITTER PADA KALANGAN MAHASISWA UNIVERSITAS KRISTEN PETRA SURABAYA - Martin Lee (Agora, 2020)
This study aims to determine wheter or not the influence of perceived brand information quality on unverified information sharing behavior through attitude towards verifying information on social media Twitter among Petra Christian University Students. The type of research used is quantitative methodology with a causal approach. The sampling technique in this study used is a purposive sampling method. The result of the study shows that perceived brand information quality significantly influences attitude towards verifying information and attitude towards verifying information also significantly influences unverified information sharing behavior.